Extended‐Release Once‐Daily Formulation of Tofacitinib: Evaluation of Pharmacokinetics Compared With Immediate‐Release Tofacitinib and Impact of Food. (6th October 2016) - Lamba, Manisha; Wang, Rong; Fletcher, Tracey; Alvey, Christine; Kushner, Joseph; Stock, Thomas C.
Abstract: Tofacitinib is an oral Janus kinase inhibitor for the treatment of rheumatoid arthritis. An extended‐release (XR) formulation has been designed to provide a once‐daily (QD) dosing option to patients to achieve comparable pharmacokinetic (PK) parameters to the twice‐daily immediate‐release (IR) formulation. We conducted 2 randomized, open‐label, phase 1 studies in healthy volunteers. Study A characterized single‐dose and steady‐state PK of tofacitinib XR 11 mg QD and intended to demonstrate equivalence of exposure under single‐dose and steady‐state conditions to tofacitinib IR 5 mg twice daily. Study B assessed the effect of a high‐fat meal on the bioavailability of tofacitinib from the XR formulation. Safety and tolerability were monitored in both studies. In study A (N = 24), the XR and IR formulations achieved time to maximum plasma concentration at 4 hours and 0.5 hours postdose, respectively; terminal half‐life was 5.9 hours and 3.2 hours, respectively. Area under plasma concentration‐time curve (AUC) and maximum plasma concentration (Cmax ) after single‐ and multiple‐dose administration were equivalent between the XR and IR formulations. In study B (N = 24), no difference in AUC was observed for fed vs fasted conditions. Cmax increased by 27% under the fed state. On repeat administration, negligible accumulation (<20%) of systemic exposures was observed for both formulations. Steady state was achieved within 48 hours of dosing with the XR formulation. Tofacitinib administration as an XR or IR formulation was generally well tolerated in these studies.